Kierunki . pismo Komitetu Porozumienia Międzyzakładowego "Solidarność", no. 21, 1982 - "Solidarność", ed. Mikołaj Niegosz and ed. committee (s.n.], 1982)
Creation and circulation: Issues no. 1-5,7,9,12-13,16(1982) contain a list of new independent periodicals.